2023
DOI: 10.3390/v15030797
|View full text |Cite
|
Sign up to set email alerts
|

B and T Cell Epitopes of the Incursionary Foot-and-Mouth Disease Virus Serotype SAT2 for Vaccine Development

Abstract: Failure of cross-protection among interserotypes and intratypes of foot-and-mouth disease virus (FMDV) is a big threat to endemic countries and their prevention and control strategies. However, insights into practices relating to the development of a multi-epitope vaccine appear as a best alternative approach to alleviate the cross-protection-associated problems. In order to facilitate the development of such a vaccine design approach, identification and prediction of the antigenic B and T cell epitopes along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 152 publications
0
2
0
Order By: Relevance
“…A considerable amount of research has been conducted to develop B- and T-cell epitope-based vaccines that protect against diseases mediated by RNA viruses [ 33 , 34 , 35 ], including FMD [ 36 ]. Here, we selected a universal B-cell epitope from the VP1 of the FMDV and designed a multi-epitope virus strain with the aim of increasing the number of neutralizing antibodies elicited that were effective against three different topotypes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A considerable amount of research has been conducted to develop B- and T-cell epitope-based vaccines that protect against diseases mediated by RNA viruses [ 33 , 34 , 35 ], including FMD [ 36 ]. Here, we selected a universal B-cell epitope from the VP1 of the FMDV and designed a multi-epitope virus strain with the aim of increasing the number of neutralizing antibodies elicited that were effective against three different topotypes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, VP2 is responsible for antigenic variations in different serotypes of FMDV. Several studies identified conserved antigenic sites in the B-C loop (residues 70–80 located between beta-strands B and C, visible on the outer surface of virus particle) and the EF loop (residues 131–134 located between beta-strands E and F, visible on the outer surface of virus particle) of serotypes O and A, and SAT viruses ( Figure 3 ) [ 55 ]. The VP2 protein has an influence on the virus replication and virulence properties.…”
Section: Adaptive Amino Acid Substitutions In Capsid Proteinsmentioning
confidence: 99%